2018
DOI: 10.1111/phor.12263
|View full text |Cite
|
Sign up to set email alerts
|

Georeferenced underwater photogrammetry to map marine habitats and submerged artificial structures

Abstract: Over the past decade, underwater photogrammetry has been experiencing an increased interest due to the enhancement of camera performance and computing power. This study describes the test of two new methods to perform georeferenced underwater photogrammetry. The first one uses the coupling between photogrammetry by scuba diving and positioning with acoustic data from a multibeam echo sounder; the second one utilises direct positioning technology with a surface floating device (photogrammetric platform). When c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Nevertheless, the usefulness and accuracy of SfM workflows are documented throughout bathymetric surveying (Abadie, Boissery, & Viala, 2018), marine archaeology (Beltrame & Costa, 2017;McCarthy & Benjamin, 2014;Skarlatos, Demestiha, & Kiparissi, 2012), ecological monitoring (Fukunaga, Burns, Craig, & Kosaki, 2019), morphometric analyses (Gutierrez-Heredia, Benzoni, Murphy, & Reynaud, 2016;Lavy et al, 2015;Napolitano, Chiariotti, & Tomasini, 2019), benthic mapping and classification (Bayley, Mogg, Koldewey, & Purvis, 2019;Leon, Roelfsema, Saunders, & Phinn, 2015;Pizarro, Friedman, Bryson, Williams, & Madin, 2017), and temporal change detection (Bennecke, Kwasnitschka, Metaxas, & Dullo, 2016;Piazza et al, 2018). The successful nature of these studies would suggest a significant opportunity to apply the SfM workflow to an ecological assessment of glass sponges and sponge reefs in the Northeast Pacific Ocean, particularly given the structural and ecological parallels that exist between glass sponge reefs and coral reefs.…”
Section: The Rise Of Sfm In Marine Ecologymentioning
confidence: 99%
“…Nevertheless, the usefulness and accuracy of SfM workflows are documented throughout bathymetric surveying (Abadie, Boissery, & Viala, 2018), marine archaeology (Beltrame & Costa, 2017;McCarthy & Benjamin, 2014;Skarlatos, Demestiha, & Kiparissi, 2012), ecological monitoring (Fukunaga, Burns, Craig, & Kosaki, 2019), morphometric analyses (Gutierrez-Heredia, Benzoni, Murphy, & Reynaud, 2016;Lavy et al, 2015;Napolitano, Chiariotti, & Tomasini, 2019), benthic mapping and classification (Bayley, Mogg, Koldewey, & Purvis, 2019;Leon, Roelfsema, Saunders, & Phinn, 2015;Pizarro, Friedman, Bryson, Williams, & Madin, 2017), and temporal change detection (Bennecke, Kwasnitschka, Metaxas, & Dullo, 2016;Piazza et al, 2018). The successful nature of these studies would suggest a significant opportunity to apply the SfM workflow to an ecological assessment of glass sponges and sponge reefs in the Northeast Pacific Ocean, particularly given the structural and ecological parallels that exist between glass sponge reefs and coral reefs.…”
Section: The Rise Of Sfm In Marine Ecologymentioning
confidence: 99%
“…In the last decade, automated aerial and close-range digital photogrammetry has become a powerful and widely used tool for three-dimensional topographic modelling [15][16][17]. Abadie et al [18] used georeferenced photogrammetry to map marine habitats on submerged artefacts. Drap et al [19] suggested that photogrammetry in underwater contexts makes it possible to obtain a comprehensive survey of all visible parts of the site without impacting the studied objects, either natural or human-made.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…SfM photogrammetry also eased the burden imposed by the awkward equipment and technical workflows of traditional photogrammetry, resulting in a surge of underwater SfM research touting SfM’s ability to capture and represent complex marine environments. Recent publications document the use of SfM for bathymetric surveying (Abadie et al., 2018), marine archaeology (Skarlatos et al., 2012; McCarthy and Benjamin, 2014; Beltrame and Costa, 2018), ecological monitoring (Fukunaga et al., 2019), morphometric analyses (Lavy et al., 2015; Gutierrez‐Heredia et al., 2016; Napolitano et al., 2019), benthic mapping and classification (Burns et al., 2015; Leon et al., 2015; Pizarro et al., 2017; Bayley et al., 2019) and monitoring temporal change (Bennecke et al., 2016; Piazza et al., 2018). For ecological analyses of marine benthos, SfM represents a non‐destructive, non‐invasive method of documentation that reduces the time spent in the field and enables objective interpretation (Piazza et al., 2018).…”
Section: Introductionmentioning
confidence: 99%